Photocatalytic-Fenton Degradation of Glycerol Solution over Visible Light-Responsive CuFe2O4 - Cheng, C. K.; Kong, Zi Ying; Khan, Maksudur R. (Springer, 2015)
The current work reports on the degradation of glycerol aqueous solution via photocatalytic-Fenton technique. The CuFe2O4 photocatalyst was synthesized via sol-gel method and its physicochemical properties were characterized. The as-synthesized photocatalyst possessed Brunauer-Emmett-Teller (BET)-specific surface area of 104 m2/g. The large BET-specific surface area was also corroborated by the field-emission scanning electron microscopy (FESEM) images which showed porous morphology. In addition, the XRD pattern showed that the visible light-active component, CuFe2O4, was successfully formed with band gap energy of 1.58 eV determined from the UV-Vis diffuse reflectance spectroscopy. Significantly, it was determined from the blank run study that the visible light was an integral part of the photoreaction. Without the visible light irradiation, glycerol degradation was low (<4.0 %). In contrast, when visible light was present, the glycerol degradation improved markedly to attain 17.7 % after 4 h of visible light irradiation, even in the absence of CuFe2O4 photocatalyst. This can be attributed to splitting of H2O2 into hydroxyl (●OH) radical. In the presence of CuFe2O4 photocatalyst, the photocatalytic Fenton degradation of glycerol has further enhanced to record nearly 40.0 % degradation at a catalyst loading of 5.0 g/l. This has demonstrated that the CuFe2O4 was capable of generating additional hydroxyl radicals to attack the glycerol molecule. Moreover, this degradation kinetics can be captured by Langmuir-Hinshelwood model from which it was found that the adsorption constant related to H2O2 was significantly weaker compared to the adsorption constant of glycerol.